Natural resources and nuclear energy development: Does political stability matter? - Dianfei Luan; Feng Yang; Muhammad Hafeez (Nuclear Engineering and Technology)
Policymakers all around the globe are focusing on the factors that can contribute to ecological sustainability. Nuclear energy is considered a sustainable and low-carbon energy source. Therefore, finding the factors that can contribute to nuclear energy development is crucial. The analysis aims to estimate the influence of natural resource rents and political stability on nuclear energy development. To obtain the estimates of these variables, we employ the CS-ARDL and PMG-ARDL methods using panel data from 1996 to 2021. The results of these methods indicate that natural resource rents hurt nuclear energy development, while political stability contributes positively to increasing investment in nuclear energy in the long run only. The controlling factors, such as economic growth and trade, also hinder nuclear growth, and financial development is instrumental in fostering nuclear energy. The short-run estimates appear to be insignificant for most of the variables. In light of these findings, we suggest that policymakers should enhance the share of nuclear energy in the energy mix via the channels of political stability and natural resource rents.